2016
DOI: 10.7314/apjcp.2015.16.18.8265
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility of "Doxorubicin and Cyclophosphamide" versus "Gemcitabine and Paclitaxel" for Treatment of Patients with Breast Cancer in Iran

Abstract: Purpose: A cost-utility analysis was performed to assess the cost-utility of neoadjuvant chemotherapy regimens containing doxorubicin and cyclophosphamide (AC) versus paclitaxel and gemcitabine (PG) for locally advanced breast cancer patients in Iran. Materials and Methods: This cross-sectional study in Namazi hospital in Shiraz, in the south of Iran covered 64 breast cancer patients. According to the random numbers, the patients were divided into two groups, 32 receiving AC and 32 PG. Costs were identified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Health care interventions are effective in treating diseases and improving the quality of life of patients; however, these interventions can lead to imposing costs on patients [ 35 37 ]. In the present study, we reported that Iranian households with an elderly person pay out of pocket an average of $8065 for medicine annually, erstwhile recorded as $92.17 per senior [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health care interventions are effective in treating diseases and improving the quality of life of patients; however, these interventions can lead to imposing costs on patients [ 35 37 ]. In the present study, we reported that Iranian households with an elderly person pay out of pocket an average of $8065 for medicine annually, erstwhile recorded as $92.17 per senior [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of our study, the mean of medical direct costs was the highest cost in both groups. Several economic evaluation showed that medical direct costs constitute the largest portion of costs among patients with CAD and other disease such as cancer [27][28][29]. The results of medical direct costs for diagnostic modalities (SPECT and stress echocardiography) showed that SPECT was more expensive than stress echocardiography ($233.3 vs $131.8).…”
Section: Discussionmentioning
confidence: 99%
“…and intensive follow-up model was not cost-effective versus standard follow-up for breast cancer from payer perspective with cost per QALY of 178,792 USD and 381,070 USD respectively [18]. Doxorubicin and Cyclophosphamide (AC) with cost per QALY of 11,554 USD was considered as a cost-effective option for the treatment of women with advanced breast cancer who were younger than 65 years old versus Gemcitabine and Paclitaxel (PG) with cost per QALY of 16,415 USD from society perspective [19]. 5-fluorouracil, doxorubicin, cyclophosphamide (FAC) was a cost effective treatment in women less than 75 years old suffering from breast cancer with node-positive versus Docetaxel with [21].…”
Section: Cancermentioning
confidence: 99%